2018
DOI: 10.1111/jcpe.12945
|View full text |Cite|
|
Sign up to set email alerts
|

Staging and grading of periodontitis: Framework and proposal of a new classification and case definition

Abstract: The paper describes a simple matrix based on stage and grade to appropriately define periodontitis in an individual patient. The proposed case definition extends beyond description based on severity to include characterization of biological features of the disease and represents a first step towards adoption of precision medicine concepts to the management of periodontitis. It also provides the necessary framework for introduction of biomarkers in diagnosis and prognosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
995
2
44

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 888 publications
(1,057 citation statements)
references
References 76 publications
16
995
2
44
Order By: Relevance
“…Patients were recruited from February 2015 to March 2016 at the University Clinic of Dentistry, Medical University of Vienna, after initial periodontal screening. The inclusion criteria, with regard to the new classification of periodontitis, were as following: localized or generalized periodontitis of periodontal stage II, III, or IV with grades B or C, age of >35 years with probing depths >5 mm in at least one site in each quadrant, radiologically detectable alveolar bone loss in all quadrants and good general health. Exclusion criteria were current pregnancy, systemic or local antimicrobial treatment in the last 6 months, periodontal treatment in the last 6 months, the presence of an infectious disease, chronic pulmonary disease, cancer, or diabetes and other apparent oral infection, intake of immunosuppressive medication or immunodeficiency.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients were recruited from February 2015 to March 2016 at the University Clinic of Dentistry, Medical University of Vienna, after initial periodontal screening. The inclusion criteria, with regard to the new classification of periodontitis, were as following: localized or generalized periodontitis of periodontal stage II, III, or IV with grades B or C, age of >35 years with probing depths >5 mm in at least one site in each quadrant, radiologically detectable alveolar bone loss in all quadrants and good general health. Exclusion criteria were current pregnancy, systemic or local antimicrobial treatment in the last 6 months, periodontal treatment in the last 6 months, the presence of an infectious disease, chronic pulmonary disease, cancer, or diabetes and other apparent oral infection, intake of immunosuppressive medication or immunodeficiency.…”
Section: Methodsmentioning
confidence: 99%
“…The activation and extent of periodontal destruction is determined on the one hand by the quantity and virulence of the bacteria, on the other by the response of the host (immune status, genetics) . Three forms of periodontitis can be distinguished, based on pathophysiology: necrotizing periodontitis, periodontitis as a direct manifestation of systemic diseases and periodontitis . Conservative periodontal treatment offers a very efficient reduction in microbial count and also improves clinical parameters .…”
Section: Introductionmentioning
confidence: 99%
“…Likewise, studies with hydroxyapatite (HA) containing oral care products reported anti‐adhesive effects, but observed no specific antimicrobial effects of the hydroxyapatite particles in situ . To evaluate those different formulations under clinical conditions, a randomized controlled study was conducted with stage I and II periodontitis patients using either a HA‐ or an AmF/SnF 2 ‐containing toothpaste for 12 weeks while receiving periodontal therapy . Results of this study showed no differences between toothpastes in reducing the visible plaque on teeth or interfering with the de novo plaque formation.…”
Section: Introductionmentioning
confidence: 99%
“…The main strengths of the present study are a larger sample size compared with previous studies, analysis of association with disease severity measured as PD ≥5 mm and sub‐analysis in AgP and CP. This showed no differences in leukocyte and erythrocyte parameters between these now obsolete disease entities, supporting the concepts that led to the elimination of AgP‐CP differentiation in the new classification . Important limitations are that no serum iron levels were studied and that this was a secondary analysis of studies not powered to test differences in erythrocyte and leukocyte parameters.…”
Section: Discussionmentioning
confidence: 56%